Assessing the Energy Efficiency of an Electric Car - František Synák; Matej Kučera; Tomáš Skrúcaný (Communications - Scientific letters of the University of Zilina, 2021)
Electric car does not supply all the electric energy, obtained from the electric network, to the wheels in the form of mechanical energy. During such a transformation, a part of this energy is lost. The article endeavours to determine the energy efficiency of selected electric car. The electric car used for measurements is not from the batch production since that is a vehicle designed at University of Zilina. The efficiency has been observed while driving under the conditions of amended methodology of New European Driving Cycle (NEDC). The measured value of electric car’s efficiency is being analyzed from the energy consumption, as well as emission production, points of view.